The Influence of School Operational Assistance (BOS) Funds on Students’ Literacy and Numeracy: Evidence from Indonesia - Wijanarko, Guritno Wahyu; Mafruhah, Izza; Hindrayani, Aniek; Muhammad Sabandi, Muhammad Sabandi (Universitas Sebelas Maret, 2025)
This study aims to analyze the effect of School Operational Assistance (BOS) fund utilization on students’ literacy and numeracy achievement through learning quality as a mediating variable. The research employs a quantitative approach using school panel data from 2022 to 2024, analyzed through the Fixed Effect Model and mediation analysis. The findings indicate that the utilization of BOS funds has a positive and significant effect on learning quality and directly as well as indirectly enhances students’ literacy and numeracy outcomes. Learning quality serves as a partial mediator that strengthens the relationship between financial support and student achievement. The novelty of this study lies in its integration of the Resource-Based View and Human Capital Theory to explain the mechanism by which financial resources are transformed into educational quality improvement. These results emphasize that the effectiveness of BOS funds depends largely on how they are managed to strengthen the quality of teaching and learning in relation to students’ literacy and numeracy outcomes. The implications of this study contribute to the advancement of educational science, particularly by enriching the understanding of effective educational resource management to improve learning quality and student achievement in Indonesia.